Workplace risk factors for cancer in the German rubber industry: Part 2. Mortality from non-respiratory cancers. Issue 5 (May 1998) - Straif, K; Weiland, S K; Werner, B; Chambless, L; Mundt, K A; Keil, U
Abstract : OBJECTIVES: To determine the mortality from non-respiratory cancers by work area among active and retired male workers of the German rubber industry. METHODS: A cohort of 11, 633 male German workers was followed up for mortality from 1 January 1981 to 31 December 1991. Cohort members were active (n = 7536) or retired (n = 4127) on 1 January 1981 and had been employed for at least one year in one of five study plants producing tyres or technical rubber goods. Work histories were reconstructed from routinely documented "cost centre codes" and classified into six categories: I preparation of materials; II production of technical rubber goods; III production of tyres; IV storage and dispatch; V general service; VI others. Standardised mortality ratios (SMRs) and 95% confidence intervals (95% CIs), controlling for age and calendar year and stratified by work area (employment in respective work area for at least one year) and time related variables (year of hire, lagged years of employment in work area) were calculated from national mortality rates as the reference. RESULTS: Significant increases in mortality were found for pharyngeal cancer in work area IV (three deaths, SMR 486, 95% CI 101 to 1419), oesophageal cancer in work area III (11 deaths, SMR 227, 95% CI 114 to 407), and leukaemia in work areas I (11 deaths, SMR 216; 95% CI 108 to 387) and II (14 deaths, SMR 187; 95% CI 102 to 213). Furthermore, increased SMRs were found for stomach cancer in work area I (22 deaths, SMR 134; 95% CI 84 to 203), colon cancer in work area II (27 deaths, SMR 131, 95% CI 86 to 191), prostatic cancer in work area V (27 deaths, SMR 152, 95% CI 99 to 221), and bladder cancer in work areas IV (six deaths, SMR 253; 95% CI 93 to 551) and V (12 deaths, SMR 159, 95% CI 82 to 279). Mortality from cancer of the liver or gall bladder, pancreas and kidney, and from lymphomas was not substantially increased in any of the work areas. CONCLUSIONS: Mortality from cancer of several sites was associated with specific work areas. Some of these associations have been reported previously. Future analyses of our study will have to determine the role of specific exposures in the aetiology of these cancers.